Safe Zones for miniscrew implant placement in different dentoskeletal patterns - Chaimanee P. (2014)
Objective: To assess the influence of different dentoskeletal patterns on the availability of interradicular spaces and to determine the safe zones for miniscrew implant placement. Materials and Methods: Periapical radiographs of 60 subjects with skeletal Class I, II, or III patterns were examined. For each interradicular site, the areas and distances at 3, 5, 7, 9, and 11 mm from the alveolar crest were measured. Results: In the maxilla, the greatest interradicular space was between the second premolar and the first molar. In the mandible, the greatest interradicular space was between the first and second molars, followed by the first and second premolars. Significant differences in interradicular spaces among the skeletal patterns were observed. Maxillary interradicular spaces, particularly between the first and second molars, in the subjects with skeletal Class II patterns, were greater than those in the subjects with skeletal Class III patterns. In contrast, in the mandible, interradicular spaces in the subjects with skeletal Class III patterns were greater than those in the subjects with skeletal Class II patterns. Conclusions: For all skeletal patterns, the safest zones were the spaces between the second premolar and the first molar in the maxilla, and between the first and second premolars and between the first and second molars in the mandible. (Angle Orthod. 2011;81:397-403.) Copyright © 2011 by The EH Angle Education and Research Foundation, Inc.